A METHOD FOR DETERMINING THE PHYSICAL PARAMETERS OF HOT SUPERGIANTS BASED ON SPECTRAL ENERGY DISTRIBUTION ANALYSIS - Alina Gyuchtash; Shakhida Nurmakhametova; Nadezhda Vaidman; Serik Khokhlov; Aldiyar Agishev; Aigerim Bakhytkyzy (Physical Sciences and Technology)
This study determines the physical parameters of B- and A-type hot supergiants through the construction and analysis of their spectral energy distributions (SEDs). These luminous stars are in the late stages of stellar evolution and are important for understanding stellar structure and the chemical evolution of galaxies. Despite the existence of earlier studies, many supergiants remain insufficiently characterized due to the complexity of observations.